Combined thermal and 6PPD-quinone stressors alter biological endpoints, oxidative stress responses, and transcriptomic profiles in the rotifer Brachionus plicatilis - Amélie Guitard; Mi-Song Hong; Jae-Seong Lee; Noelle Babin; Carter Eagles; Jeonghoon Han; Chang-Bum Jeong; Jordan Jun Chul Park (Journal of Hazardous Materials, 2026)

Comparative effects of the two copper compounds: Copper chloride and copper sulfate on bioaccumulation, fecundity, and stress responses in the brine shrimp Artemia franciscana - Eunseong Lee; Chaehwan Park; Ji-Yeon Hyeon; Jordan Jun Chul Park; Kongtae Ra; Young-Ung Choi; Jeonghoon Han (Marine Pollution Bulletin, 2026)

Erratum: Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2025)

Pilot-Scale Cultivation of Seaweed (Undaria pinnatifida) Along an Offshore Wind Farm in Southwestern Korea - Dongmun Choi; Hyung-Gon Lee; Yun-Hwan Jung; Dae-Won Lee; Jeonghoon Han; Ji-Yeon Hyeon; Young-Ung Choi (Journal of Marine Science and Engineering, 2025)
Marine environments provide a unique opportunity to blend offshore wind energy production and marine fishery activities as complementary technologies. This study investigated the morphological characteristics (length and weight) and biomass yield of seaweed (Undaria pinnatifida) in a model marine environment with mariculture within an offshore wind farm in southwestern Korea. The mean lengths in the first cultivation trials of U. pinnatifida sporophytes increased from 1.8 ± 0.1 cm in November 2021 to 120–170 cm in March 2022 (density, 39.8 plants m−1; final wet weight, 98.6–249.1 g (mean 146.8 ± 20.4 g, n = 20 ind.); yield 5842 g m−1). Further, for the second cultivation trial, the length of the sporophytes increased from 1.5 ± 0.1 cm in November 2021 to 120–150 cm in April 2022 (density, 49.3 plants m−1; final wet weight, 83.0–251.6 g (mean 155.7 ± 19.0 g; n = 20 ind.); yield, 7676 g m−1), and, owing to the increase in water temperature and light intensity due to seasonal changes around the offshore wind power farm, the second cultivation trials showed signs of chlorosis. Considering the environment, we judged seaweed growth to be normal. Therefore, when applying this model to grow U. pinnatifida, seasonal temperature changes, the purpose of the product, and the nutritional status of the open-sea area should be considered. These results may improve seaweed farming in offshore wind farms in the future.

Effects of temperature changes on oxidative stress and antioxidant defense system in the Zhikong scallop Chlamys farreri - Jin Ah Song; Eunseong Lee; Young-Ung Choi; Jordan Jun Chul Park; Jeonghoon Han (Fisheries Science, 2025)

Quantitative Real-Time Polymerase Chain Reaction (PCR) Assay for Rapid Monitoring of the Harmful Algal Bloom Species Cochlodinium polykrikoides - Min-Jeong Kim; Hyun-Jung Kim; Joon Sang Park; Donhyug Kang; Sungho Cho; Hansoo Kim; Seung Ho Baek; Jordan Jun Chul Park; Jeonghoon Han; Kang Eun Kim; Seung Won Jung (Journal of Marine Science and Engineering, 2025)
Harmful blooms of the dinoflagellate Cochlodinium polykrikoides (Margalefidinium polykrikoides) had detrimental aquacultural and economic effects globally, and to reduce the damage caused by these blooms, early biomonitoring and quantitative analysis of C. polykrikoides are of the utmost importance. Here, for the detection of C. polykrikoides using quantitative real-time polymerase chain reactions, we developed specific primers targeting the large subunit ribosomal DNA (LSU rDNA) and evaluated their applicability in the field during the occurrence of a C. polykrikoides bloom. The specific primers not only accurately detected C. polykirkoides but also had a detection performance comparable with that obtained using microscopic observations. Accordingly, we developed a system that can be used in the field and applied when red tides occur, with accurate results being obtained more than five times more rapidly than those obtained based on microscopic analysis. Collectively, our findings indicate that the C. polykrikoides bloom detection system developed in this study can be applied to rapidly detect and accurately quantify C. polykrikoides in environmental samples. Data obtained using this system could be used as a basis for developing prompt monitoring and warning systems for the early detection of C. polykrikoides blooms in the field.

Effects of Zooplankton Extracts on the Production of Paralytic Shellfish Toxins by Gymnodinium catenatum and Alexandrium pacificum - Jae Yeon Park; Dong Han Choi; Na Yeong Kim; Myung Jin Hyun; Young-Eun Kim; Jae-Hoon Noh; Jung-Rae Rho; Bum Soo Park; Seongjin Hong; Sea-Yong Kim; Mungi Kim; Jeonghoon Han; et al. (Ocean Science Journal, 2024)

Complete Mitogenomes of Deep-Sea Eels Histiobranchus bathybius and Simenchelys parasitica and a New Record of H. bathybius from the East Mariana Basin, Western Pacific Ocean - Jeonghoon Han; Han-Jun Kim; Byung-Jik Kim; Ji-Yeon Hyeon; Choong Hwan Noh; Young-Ung Choi (Journal of Marine Science and Engineering, 2024)
In this study, using Illumina sequencing, we sequenced first the complete mitochondrial genome (mitogenome) of two deep-sea eels, Histiobranchus bathybius and Simenchelys parasitica, collected from the East Mariana Basin in the Western Pacific Ocean. The complete length of the H. bathybius and S. parasitica mitogenomes were 16,696 and 16,687 bp, respectively, each containing 37 genes (13 protein-coding genes, 22 tRNA genes, and 2 ribosomal RNA genes). To enhance the accuracy of the identification of H. bathybius and S. parasitica, we performed a phylogenetic analysis of multiple deep-sea eels based on the mitochondrial DNA gene (cytochrome c oxidase subunit I [COI]) using the maximum likelihood method. Our phylogenetic tree analysis confirmed that the specimens collected in this study are congeneric species of H. bathybius and S. parasitica reported in previous studies. Based on these results, we report the first complete mitogenomes of H. bathybius and S. parasitica and a new record for the two species in the East Mariana Basin.

Climate-related variabilities in the Styx-M ice core record from northern Victoria Land, East Antarctica, during 1979–2014 - Yalalt Nyamgerel; Yeongcheol Han; Heejin Hwang; Changhee Han; Sang-Bum Hong; Soon Do Hur; Jeonghoon Lee (Science of The Total Environment, 2024)

Isotopic evolution of snowmelt and its hydrometeorological importance in snow-covered regions - Yalalt Nyamgerel; Yeongcheol Han; Jeonghoon Lee (CATENA, 2024)

On the Species Identification of Korean Geoduck Clam (Panopea sp. 1) Based on the Morphological and Molecular Evidence - Jeonghoon Han; Jong Guk Kim; O-Nam Kwon; Jordan Jun Chul Park; Kyun-Woo Lee; Young-Ung Choi (Journal of Marine Science and Engineering, 2023)
The geoduck clam is a high-value species in South Korea. However, the molecular and morphological characteristics of geoduck clams from the southern coast of South Korea remain unexamined. The accurate identification of native geoduck clams is crucial for their conservation and management. Therefore, this study used a combination of molecular and morphological analyses to characterize native geoduck clams from the southern coast of South Korea. Based on complete mitochondrial genome and morphological analyses, the native species of geoduck clam from this study area was identified as Panopea sp. 1. The complete mitochondrial genome sequencing of Panopea sp. 1 revealed a total of 16,225 bp in length with 37 genes (13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes). It was also shown that Panopea sp. 1 belongs to the family Hiatellidae based on a phylogenetic analysis tree with 11 bivalve species. In particular, Panopea sp. 1 is closely related to three other Panopea species (Panopea sp., Panopea abrupta, and Panopea japonica). The phylogenetic analysis correlated with the morphological analysis. Overall, this is the first reliable record of Panopea sp. 1 in South Korea. These findings provide a basis for accurate species identification based on morphological characteristics and complete mitochondrial genome sequencing.

Offshore Wind Farms in South Korea: A Potential Site for Scallop Culture - Dae-Won Lee; Sung-Yong Oh; Jordan Jun Chul Park; Yun-Hwan Jung; Han-Jun Kim; Dong Mun Choi; Young-Ung Choi; Jeonghoon Han (Journal of Marine Science and Engineering, 2023)
Owing to the constant wind generated by the vast ocean, energy production from offshore wind farms (OWFs) plays an important role in the expansion of renewable energy. However, areas close to large wind farms are often left unutilized, and aquaculture farmers find it difficult to efficiently utilize these unoccupied spaces due to limited information showing the feasibility of utilization of OWFs as potential scallop culture sites. To analyze whether the two scallop species Zhikong scallop (Chlamys farreri) and bay scallop (Argopecten irradians) can be grown at OWFs of Gochang and Buan, Jeollabuk-do, Republic of Korea, the growth characteristics of the two scallop species were analyzed and compared with those grown at the Tongyeong Megacosm Test Station. The results clearly showed that the growth of scallops at the OWF was significantly lower with respect to the shell lengths, height, width, and weight, compared to those grown at the megacosm station. However, scallops grown at the OWF still showed consistent growth in parallel with those grown at the megacosm test station. Yet, there was a species-specific mortality rate between the two sites. In addition, our results suggest that temperature may be a key determinant of the growth of C. farreri and A. irradians. Overall, this study contributes to establishing a foundation for the stable and continuous farming of marine bivalves (e.g., clams, oysters, mussels, and scallops) in OWF areas.

Complete Mitochondrial DNA Genomes of Deep-Sea Eels Synaphobranchus brevidorsalis and S. affinis and New Record of S. brevidorsalis from the East Mariana Basin - Jeonghoon Han; Han-Jun Kim; Kyun-Woo Lee; Young-Ung Choi (Journal of Marine Science and Engineering, 2023)
In this study, we document the first recorded range extension of the genus Synaphobranchus from the East Mariana Basin in the Western Pacific Ocean. We sequenced the complete mitochondrial (mt) genome of two deep-sea eels (Synaphobranchus brevidorsalis and S. affinis) collected in the East Mariana Basin in the Western Pacific Ocean. The complete mt genomes of S. brevidorsalis and S. affinis were 16,686 bp and 16,677 bp in length, respectively, and consisted of 13 protein-coding genes, 22 tRNA genes, and two rRNA genes. Molecular phylogenetic analysis of the two deep-sea eel species was performed, based on the mt cytochrome c oxidase subunit I (COI) gene using the maximum likelihood method. The molecular phylogenetic tree demonstrated that S. brevidorsalis and S. affinis were congeneric species of S. brevidorsalis and S. affinis reported in previous studies with bootstrap values of 100% and 100%, respectively. This is the first report on the complete mt genomes of S. brevidorsalis and S. affinis collected in the East Mariana Basin in the Western Pacific Ocean. Overall, our study highlights the potential of molecular approaches in identifying species diversity and distribution in the Western Pacific Ocean.

New Record of Geoduck Clam Collected from the East Coast of South Korea and Its Reproductive Characteristics - Jeonghoon Han; Jong Guk Kim; O-Nam Kwon; Young-Ung Choi (Journal of Marine Science and Engineering, 2023)
Geoduck clams are important commercial marine resources in Southeast Asia. However, the complete mitochondrial genome of the native geoduck clam in South Korea has not been reported yet. This study reports a geoduck clam collected from the east coast of South Korea. Based on its morphological characteristics and molecular data, the geoduck clam was identified as Panopea sp. belonging to the bivalve family Hiatellidae. We determined the complete mitochondrial genome of this species and investigated the seasonal reproductive pattern for monthly changes in sex ratio, gametogenesis, and reproductive cycle from September 2019 to August 2020. The total length of the complete mitochondrial genome sequence is 16,006 bp, containing 13 protein-coding, 22 transfer RNA, 2 ribosomal RNA, and a control region (D-loop). A molecular phylogenetic comparison with 10 bivalve species showed that the geoduck clam specimen belongs to the family Hiatellidae, clustering with Panopea abrupta Chinese strain, P. generosa, and P. globosa. The gametogenesis of the geoduck clam was identified in six stages by histological analysis. The sex ratio was biased towards males from May 2019 to July 2019, the main spawning activity from the frequency of the gonads with ripe and spent stages occurred from October 2018 to April 2019, and there was no clear pattern of spawning peaks from May to August 2019 with gonads developed asynchronously between both sexes. This is the first study to report new records of the genus Panopea based on the complete mitochondrial genome and to examine the seasonal reproductive pattern of the native geoduck clam Panopea sp. in South Korea, providing valuable information for its sustainable management in South Korea.

Identification of nitrate sources in tap water sources across South Korea using multiple stable isotopes: Implications for land use and water management - Hyejung Jung; Yun S. Kim; Jisu Yoo; So Jeong Han; Jeonghoon Lee (Science of The Total Environment, 2023)

New Record of the Grey Cutthroat, Synaphobranchus affinis (Anguilliformes: Synaphobranchidae) from the East Mariana Basin, Western Pacific Ocean - Jeonghoon Han; Han-Jun Kim; Byung-Jik Kim; Kiseong Hyeong; Choonghwan Noh; Young-Ung Choi (Journal of Marine Science and Engineering, 2022)
Two deep-sea eels collected from the East Mariana Basin in the western Pacific Ocean are described in this study. Based on their morphological features, two eel specimens were assumed to belong to the Gray cutthroat eel family, Synaphobranchidae. Mitochondrial DNA (mtDNA) genes have been widely used as genetic markers to identify fish species. To accurately identify the species of the two eel specimens, we sequenced the mitochondrial cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) genes from the two eel specimens. The sequences from the specimens were 100% identical. The molecular phylogenetic tree confirmed that the two eel specimens were closely related to Synaphobranchus affinis with a bootstrap value of 100%. This is the first study to report new records of S. affinis from the East Mariana Basin in the western Pacific Ocean.

An optimal strategy for determining triple oxygen isotope ratios in natural water using a commercial cavity ring-down spectrometer - Songyi Kim; Changhee Han; Jangil Moon; Yeongcheol Han; Soon Do Hur; Jeonghoon Lee (Geosciences Journal, 2022)

Reproductive Characteristics of the Flat Oyster Ostrea denselamellosa (Bivalvia, Ostreidae) Found on the Southern Coast of South Korea - Jeonghoon Han; Han-Jun Kim; Sung-Yong Oh; Young-Ung Choi (Journal of Marine Science and Engineering, 2022)
In this study, we investigated the reproductive pattern of the commercially and ecologically important species, Ostrea denelamellosa, to inform stock management strategies in South Korea. Prior to the reproduction experiment, the complete mitochondrial (mt) genome of the flat oyster, Ostrea denselamellosa, was analyzed using next-generation sequencing technology. Then, to determine the reproductive pattern of Ostrea denselamellosa, we investigated monthly changes in the gametogenesis, reproductive cycle, and sex ratio from January to October 2021 in females. The total length of the mt genome sequence of O. denselamellosa was 16,225 bp and contained 37 genes (13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes). Molecular phylogenetic comparison with 20 known species of Pteriomorphia showed that O. denselamellosa belongs to the family Ostreidae. In addition, O. denselamellosa clustered together with the O. denselamellosa Chinese strain, with a bootstrap value of 100%. Histological analysis indicated a discrepancy in gamete development of O. denselamellosa with synchronous maturation of oocytes and asynchronous development of spermatozoa in gonads. The spawning activity occurred between May and September with a temperature range gap of 6.5 °C. The spawning activity occurred from May when the temperature reached 16.7 °C until September when the temperature dropped below 23.2 °C. Furthermore, sex ratio bias was observed. This is the first study to report the complete mt genome sequence and examine the reproductive pattern in native O. denselamellosa in South Korea. Overall, these findings will help enhance the knowledge for the management and sustainable fishery of endangered oyster species including O. denselamellosa in the South Sea of Korea.

Seasonal Variations in the Fish Species Composition and Community Structures on the Eastern Coast of South Korea - Jeonghoon Han; Young-Ung Choi (Journal of Marine Science and Engineering, 2022)
The seasonal variations in the species composition of set net fisheries were investigated on the Eastern coast of Korea, from 2007 to 2008. In total, 51 species were found that were classified into 15 orders and 33 families. The water temperature of the study area was 0.1–1.8 °C in 2007 and 0.6–2.1 °C in 2008, which was higher than the average water temperature in the previous decade. The monthly variation in the number of species peaked twice, in May (spring) and November (autumn) when the water temperature increased and decreased, respectively, and the monthly variation in the number of individuals showed a remarkably high trend in winter and autumn and was mainly caused by large migratory species. Based on the cluster analysis of the 18 most dominant species with more than 0.4% of the total number of individuals, we divided the species composition and community structures into three groups: fishes with a temporary appearance (Group A), fishes with a long-term appearance (Group B), and dominant pelagic fishes appearing with a long-term appearance (Group C). We could conclude that the seasonal variation in the structure of the fish community was mainly caused by the pelagic migration of species under high water temperature conditions during the study period.

Effects of Leachates from Hydrothermal Ore Particulates on Life Cycle Parameters and Expression of Defense-Related Genes in the Marine Copepod Tigriopus japonicus - Jeonghoon Han; Yeun Park; Hyeryeong Jeong; Sang Bae Kim; Chan Min Yoo; Kiseong Hyeong; Kyun-Woo Lee (Water, Air, & Soil Pollution, 2022)

Characterization of bacterial community structure in two alcyonacean soft corals (Litophyton sp. and Sinularia sp.) from Chuuk, Micronesia - Joon Sang Park; Jeonghoon Han; Sung-Suk Suh; Hyun-Jung Kim; Taek-Kyun Lee; Seung Won Jung (Coral Reefs, 2022)

New records of two deep-sea eels collected from the Western Pacific Ocean based on COI and 16S rRNA genes - Han-Jun Kim; Jeonghoon Han; Byung-Jik Kim; Kyun-Woo Lee; Kiseong Hyeong; Young-Ung Choi (Molecular Biology Reports, 2021)

Identification and response of cytochrome P450 genes in the brackish water flea Diaphanosoma celebensis after exposure to benzo[α]pyrene and heavy metals - Jeonghoon Han; Kyun-Woo Lee (Molecular Biology Reports, 2021)

Effects of temperature shifts on life parameters and expression of fatty acid synthesis and heat shock protein genes in temperate and Antarctic copepods Tigriopus japonicus and Tigriopus kingsejongensis - Jeonghoon Han; Min-Chul Lee; Jun Chul Park; Sanghee Kim; Jae-Seong Lee (Polar Biology, 2018)

Effects of temperature changes on the generation of reactive oxygen species and the expression and activity of glutathione-S transferases in two congeneric copepods Tigriopus japonicus and Tigriopus kingsejongensis - Jeonghoon Han; Chang-Bum Jeong; Eunjin Byeon; Jae-Seong Lee (Fisheries Science, 2018)

Effects of temperature on growth and fatty acid synthesis in the cyclopoid copepod Paracyclopina nana - Seung-Hwi Lee; Min-Chul Lee; Jayesh Puthumana; Jun Chul Park; Sujin Kang; Jeonghoon Han; Kyung-Hoon Shin; Heum Gi Park; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2017)

Acute Toxicity of Gamma Radiation to the Monogonont Rotifer Brachionus koreanus - Eun-Ji Won; Jeonghoon Han; Atsushi Hagiwara; Shoji Oda; Hiroshi Mitani; Jae-Seong Lee (Bulletin of Environmental Contamination and Toxicology, 2016)

Identification of insulin-like peptide 1 (ILP1) gene and its expression in response to different food sources in the intertidal copepod Tigriopus japonicus - Min Chul Lee; Eun-Ji Won; Seung-Hwi Lee; Dae-Sik Hwang; Hui-Su Kim; Jeonghoon Han; Jae-Sung Rhee; Ae-Son Om; Jae-Seong Lee (Fisheries Science, 2015)

Ecotoxicity of triphenyltin on the marine copepod Tigriopus japonicus at various biological organisations: from molecular to population-level effects - Andy Xianliang Yi; Jeonghoon Han; Jae-Seong Lee; Kenneth M. Y. Leung (Ecotoxicology, 2014)

Sequence analysis of genomic DNA (680 Mb) by GS-FLX-Titanium sequencer in the monogonont rotifer, Brachionus ibericus - Jae-Seong Lee; Ryeo-Ok Kim; Jae-Sung Rhee; Jeonghoon Han; Dae-Sik Hwang; Beom-Soon Choi; Chang Joo Lee; Yong-Dal Yoon; Jong-Sung Lim; Young-Mi Lee; Gyung Soo Park; Atsushi Hagiwara; et al. (Hydrobiologia, 2011)